EVALUATING THE EFFICACY OF CITRONELLA ESSENTIAL OIL (Cymbopogon nardus) AS A CONTROL AGENT FOR WAREHOUSE RICE WEEVIL (Sitophilus oryzae) - Hariani, Nova; Lestari, Rina; Zulfitri, Apriwi (Universitas Tanjungpura, 2024)
Sitophilus oryzae or rice weevil is a primary pest of rice that is very detrimental. Pest control that is usually carried out is fumigation using phosphine gas and fumigation using methyl bromide. The use of insecticides has several negative impacts on humans and the environment, so it is necessary to control pests naturally, namely using citronella essential oil. Citronella essential oil contains high levels of citronella and geraniol compounds and these compounds are contact toxic and antifeedant against insects. This research aims to determine the effect of citronella essential oil on mortality using the fumigation method and the response of rice lice to citronella essential oil in the flourdisc bioassay test. This research was carried out at the insect pest control and biodetriosation and formulation laboratory, using a completely randomized plan. The results showed that citronella oil was classified as effective in controlling the population of S. oryzae with a mortality of 41% using fumigation method and had anti-feedant properties compared to the control in the flour disk assay test. In the flourdisc bioassay method, the percentage of 2 gr/L influences the low relative growth rate, relative consumption rate and conversion efficiency of consumed food and the food prevention index continues to increase. Citronella essential oil has potential and effectiveness as a control for the warehouse pest rice weevil (Sitophilus oryzae).